A Detached Leaf Culture Technique for Resistance Screening Against Bacterial Pustule in Soybean - Preecha Surin; Nalinee Srivakorn; Bruce Imrie; Robert Lawn (Agriculture and Natural Resources, 1993)
A series of experiments was conducted to obtain information on variation in virulence of Xanthomonas campestris pv. glycines, the causal organism of bacterial pustule, resistance of the soybean (Glycine max) host, and methods of screening for resistance. Variation was found in both virulence and resistance. It was concluded that, given the levels of variability detected, use of a detached leaf technique with inoculation by a pinprick method would be the most effective means of selecting for resistance.